Money of the Indonesian Republic of Banten as a Form of Struggle to Defend Indonesian Independence (1947-1949) - Hanita, Clarisa Dwi; Maryuni, Yuni; Putra, Arif Permana (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The writing is motivated by the history of Indonesian currency after independence which is not well recorded. The purpose of the writing is to find facts on (1) the history of the Republic of Indonesia Banten Regional Currency (URIDAB) in 1947-1949; (2) the political and economic influence of the Republic of Indonesia Banten Regional Currency (URIDAB) for the Banten community in the struggle to maintain Indonesian independence in 1947-1949. The writing of the thesis uses the historical method through four stages, namely heuristics, source criticism, interpretation, historiography. The results of the study show that the arrival of the Dutch made the political and economic conditions of Indonesia after independence very chaotic in the midst of the conditions of the newly independent Indonesia. These conditions fostered enthusiasm for the central government in Yogyakarta and the Banten Residency community and became a factor in the printing of URIDAB. The influence of URIDAB in the political field is the main symbol of an independent country and as a tool of struggle. In the economic field, it is as a legal tender and regulates price control.